Increasing knowledge about nutrition and health in the elderly and cadres in Banguntapan Village, Bantul - Mae Sri Hartati Wahyuningsih; Dwi Aris Agung Nugrahaningsih; Probosuseno Probosuseno (Journal of Community Empowerment for Health, 2020)
Increase the number of elderly is one of the social problems that require the attention of all involved parties. Health care efforts are now aimed at keeping the elderly healthy, active, independent, and productive socially and economically for themselves, their families and the community. Elderly is an age group where a person has experienced various decreases in body functions that can affect appetite, which ultimately leads to malnutrition. We designed community service-based study to increase the elderly health in the Banguntapan Village through increasing the awareness of the elderly about managing their health, the knowledge and skill to take care elderly of the families who have elderly on their care in Banguntapan Village. The method applied in this activity is counseling with pre-test and the first post-test and distribution pocket of about nutrition and elderly health. To be able to measure the retained knowledge after the activities, we also carried out the second post-test four weeks after the first meeting. The data were analyzed by descriptive analysis, and a paired t-test was performed to test the pre-test and post-test data. The total participants who participated in this activity were 144 people consisting of all cadres in Banguntapan Village, plus the elderly and families who have elderly in Karangbendo Hamlet. This research showed that there was an increase in knowledge about health and nutrition between the 1st pretest-posttest; between the 1st post-test and 2nd post-test; and between the second pretest and posttest (11.14; 14.86; 28.03)%. The counseling, discussion, and distribution of pocketbooks can increase the knowledge of the elderly, family and volunteer in Banguntapan and Karang Bendo Village.